DIGITAL MARKETING DURING COVID 19: JORDANIAN VIEWPOINT. - Khaled (M.K) Ismail Alshake Theep (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Changes were activated by the Covid 19 pandemic, such as encouraging digital networking and marketing campaigns. The goal of this paper is to analyse the possible benefits and implications of digital marketing within the growing epidemic timeframe and to develop the Islamic concept of digital marketing from a religious perspective. A descriptive methodology will be used in the analysis process used in the article by researching various digital marketing literature. The research shows that IT has had a major effect on digital marketing, particularly during the outbreak of Covid-19. From an Islamic point of view, an examination of digital marketing will have significant consequences for academics. Sensitive to the fundamental ontology and epistemology, the paper would examine Islamic marketing. This paper advances digital marketing from an Islamic perspective by presenting observational studies into digital marketing and Islamic marketing. Companies will look for innovative marketing strategies in the future by integrating new innovations.